Effect Of Interest Rate, Inflation, Profit-Sharing, And Branch Network On Mudharabah Deposits Of Islamic Commercial Banks In Indonesia - Yusuf Zaini Aprizal (Journal of Islamic Business and Economic Review, 2021)
The study aimed to analyze and find out the effect of variables of interest rate, inflation, profit-sharing and branch network on mudharabah deposit of Islamic Commercial Banks in Indonesia, both simultaneously and partially. Population in this study was Islamic Commercial Bank registered with the Financial Services Authority with a research period of 2014-2018. The data analysis method used was panel data regression analysis using Eviews data processing applications. Testing was conducted using the level of sig. α = 0.05. The results of this study indicated that the simultaneous variable interest rates, inflation, profit-sharing, and branch networks significantly influenced mudharabah deposits. This was indicated by the significance value obtained at 0.0000. Partially only profit-sharing and branch network variables affected mudharabah deposits with significance values obtained 0.0087 and 0.0000. While the variable interest rates and inflation had no effect toward mudharabah deposits, this was indicated by the significance value of 0.5011 and 0.2061. The conclusion of this study is that in a good economic condition, the general public in investing mudharabah deposits would look more at the internal factors of Islamic banking. Therefore, supervision, strengthening and improving services are very important to make Islamic banks can raise more public funds.